ANALISIS PENGARUH GAYA KEPEMIMPINAN, KEPUASAN KERJA TERHADAP KINERJA TENAGA KEPENDIDIKAN - Warsi, Diah Aryanti Sapto; Siswanta, Lilik; Wahyuni, Endang Tri; Sukhemi, Sukhemi (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2020)
The purpose of this study is to analyse and prove the influence of leadership style, job satisfaction on the employees performance at the University of PGRI Yogyakarta. The total sample of 56 respondents drawn using proportional random sampling, and data analysis techniques using Structural Equations Modeling (SEM) with the help of PLS software. The results of the study explained that occurred a significant effecy on the latent exogenous variables that influence leadership style, job satisfaction in improving the performance of (endogenous latent variables). This is demonstrated by the significant figures and valid in every model tested.